2016
DOI: 10.21786/bbrc/9.3/17
|View full text |Cite
|
Sign up to set email alerts
|

Biotyping and antibiogram of Riemerella anatipestifer from ducks in Kerala

Abstract: New duck disease caused by Riemerella anatipestifer is a new disease emerged in Kerala from 2008 onwards. Six R. anatipestifer isolates responsible for the disease were isolated from suspected ducks from different outbreak areas of the state and were identifi ed. Since the ecological, morphological and cultural characteristics of R. anatipestifer are more or less similar to Pasteurella multocida, the disease is often confused with duck pasteurellosis and misdiagnosed. R. anatipestifer infection is also charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 20 publications
2
3
0
Order By: Relevance
“…Amikacin, florfenicol, and doxycycline were the drugs of choice for the tested isolates. These results followed those of Priya et al [ 29 ] and Surya et al [ 22 ]. Unfortunately, the indiscriminate use of antimicrobials in feed, both to promote growth and as a preventive strategy, led to significant resistance to almost all practical antibiotics.…”
Section: Discussionsupporting
confidence: 91%
“…Amikacin, florfenicol, and doxycycline were the drugs of choice for the tested isolates. These results followed those of Priya et al [ 29 ] and Surya et al [ 22 ]. Unfortunately, the indiscriminate use of antimicrobials in feed, both to promote growth and as a preventive strategy, led to significant resistance to almost all practical antibiotics.…”
Section: Discussionsupporting
confidence: 91%
“…This confirmed the results obtained by Hinz et al [3], who observed β-haemolysis on agar in over 20% of isolates after 24-48 h of incubation. The ability of R. anatipestifer strains to induce haemolysis has also been observed by other researchers [9,25,26]. The biochemical properties of R. anatipestifer are often variable.…”
Section: Discussionsupporting
confidence: 56%
“…R. anatipestifer, together with Riemerella columbina (R. columbina) and Riemerella columbipharyngis (R. columbipharyngis), currently form the separate genus Riemerella, belonging to the family Weeksellaceae [5,6]. Septicaemia anserum exsudativa, caused by R. anatipestifer, is a disease common in many Asian countries with intensive rearing of ducks and geese [7][8][9]. The infection affects young birds, especially those at 1 to 8 weeks of age [2].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the regular use in the treatment or as feed additives, the gradual development of sulfadiazine resistance among the R. anatipestifer isolates was also recorded. Ofloxacin and cefotaxime were also previously recorded as ineffective for R. anatipestifer isolates (Surya et al 2016).…”
Section: Antimicrobial Resistance Pattern Of the Isolatesmentioning
confidence: 96%
“…The loss of capsules following sub-cultivation might be a probable explanation for rendering circulated P. multocida in animal environments untypable (Dziva et al 2008). Among the available literature from India, a low recovery rate of R. anatipestifer from suspected cases of duck septicemia was reported by Surya et al (2016). A previous investigation, considered to be the first information from Assam on the prevalence of duck septicemia-like disease revealed recovery of R. anatipestifer from ocular and pharyngeal swabs of clinically affected ducks (Hazarika et al 2020).…”
Section: Isolation and Molecular Characterization Of P Multocida And...mentioning
confidence: 99%